2014
DOI: 10.2967/jnumed.114.140038
|View full text |Cite
|
Sign up to set email alerts
|

Improved Modeling of In Vivo Kinetics of Slowly Diffusing Radiotracers for Tumor Imaging

Abstract: Large-molecule tracers, such as labeled antibodies, have shown success in immuno-PET for imaging of specific cell surface biomarkers. However, previous work has shown that localization of such tracers shows high levels of heterogeneity in target tissues, due to both the slow diffusion and the high affinity of these compounds. In this work, we investigate the effects of subvoxel spatial heterogeneity on measured time–activity curves in PET imaging and the effects of ignoring diffusion limitation on parameter es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…To accomplish this comparison of methods, we used 64 Cu-NODAGA-PSMA-IgG and 64 Cu-NODAGA-PSMA-Mb as radiotracers for imaging in our preclinical model system. Previous studies have shown that the optimal signalto-background ratios are attainable within a window of 12-48 h with formats of imaging probes similar to those in this study (ViolaVillegas et al (37); Wilks et al (38)). The radiotracers were administered intravenously to cohorts of 5 mice harboring bilateral PSMA-positive CWR22Rv1 and PSMAnegative PC-3 xenografts and serially imaged up to 48 and 72 h for the 64 Cu-NODAGA-PSMA-Mb and 64 Cu-NODAGA-PSMAIgG, respectively.…”
Section: Comparison Of CLI and Pet For Imaging Psma-positive Tumor Xesupporting
confidence: 67%
“…To accomplish this comparison of methods, we used 64 Cu-NODAGA-PSMA-IgG and 64 Cu-NODAGA-PSMA-Mb as radiotracers for imaging in our preclinical model system. Previous studies have shown that the optimal signalto-background ratios are attainable within a window of 12-48 h with formats of imaging probes similar to those in this study (ViolaVillegas et al (37); Wilks et al (38)). The radiotracers were administered intravenously to cohorts of 5 mice harboring bilateral PSMA-positive CWR22Rv1 and PSMAnegative PC-3 xenografts and serially imaged up to 48 and 72 h for the 64 Cu-NODAGA-PSMA-Mb and 64 Cu-NODAGA-PSMAIgG, respectively.…”
Section: Comparison Of CLI and Pet For Imaging Psma-positive Tumor Xesupporting
confidence: 67%
“…Although radiolabeled antibodies are a powerful tool in the drug development process, antibody-based immuno-PET radiotracers have several clinical drawbacks including long clearance times and high background signal, which require patients to return to the hospital several days after radiotracer injection for imaging (29,30). Furthermore, we have recently shown that anti-PD-L1 antibodies have limited tumor penetration (31) and that the Fc region of anti-PD-L1 monoclonal antibodies can mediate unintended T cell depletion (27).…”
Section: Discussionmentioning
confidence: 99%
“…3C). Both tumor types demonstrated significant heterogeneity in the distribution of the antibody signal ( 111 In), as expected for compounds of high molecular weight (19,20).…”
Section: Demonstration Of Differential Distribution Of Mmae In Gcc-nementioning
confidence: 73%